Aldiminium and 1,2,3-triazolium dithiocarboxylate zwitterions derived from cyclic (alkyl)(amino) and mesoionic carbenes - Touj, Nedra; Mazars, François; Zaragoza, Guillermo; Delaude, Lionel (Beilstein Journal of Organic Chemistry, 2023)
The synthesis of zwitterionic dithiocarboxylate adducts was achieved by deprotonating various aldiminium or 1,2,3-triazolium salts with a strong base, followed by the nucleophilic addition of the in situ-generated cyclic (alkyl)(amino) or mesoionic carbenes (CAACs or MICs) onto carbon disulfide. Nine novel compounds were isolated and fully characterized by 1H and 13C NMR, FTIR, and HRMS techniques. Moreover, the molecular structures of two CAAC·CS2 and two MIC·CS2 betaines were determined by X-ray diffraction analysis. The analytical data recorded for all these adducts were compared with those reported previously for related NHC·CS2 betaines derived from imidazolinium or (benz)imidazolium salts. Due to the absence of electronic communication between the CS2 unit and the orthogonal heterocycle, all the CAAC·CS2, MIC·CS2, and NHC·CS2 zwitterions displayed similar electronic properties and featured the same bite angle. Yet, their steric properties are liable to ample modifications by varying the exact nature of their cationic heterocycle and its substituents.
Keywords: betaines; carbenes; ligand effects; nitrogen heterocycles; zwitterions